2010
DOI: 10.1002/nbm.1486
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of renal ischemia reperfusion injury in an experimental model

Abstract: Renal ischemia reperfusion injury (IRI) is a major cause of acute renal failure. It occurs in various clinical settings such as renal transplantation, shock and vascular surgery. Serum creatinine level has been used as an index for estimating the degree of renal functional loss in renal IRI. However, it only evaluates the global renal function. In this study, diffusion tensor imaging (DTI) was used to characterize renal IRI in an experimental rat model. Spin-echo echo-planar DTI with b-value of 300 s/mm(2) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 41 publications
(48 reference statements)
3
49
0
Order By: Relevance
“…With pancreatic microcirculation ischemia aggravated, pancreatic glandular tissue appears necrosis and liquefaction, which restricts water molecules diffuse movement and reduces anisotropy diffusion of extracellular water molecules. Similarly, Cheung et al[37] found that both ADC and FA of kidney medulla in renal ischemia reperfusion injury were significantly less (p < 0.01) than those of contralateral intact medulla. Therefore, our results showed that ADC and FA values might be a supplementary indicator for determining the severity of AP.…”
Section: Discussionmentioning
confidence: 84%
“…With pancreatic microcirculation ischemia aggravated, pancreatic glandular tissue appears necrosis and liquefaction, which restricts water molecules diffuse movement and reduces anisotropy diffusion of extracellular water molecules. Similarly, Cheung et al[37] found that both ADC and FA of kidney medulla in renal ischemia reperfusion injury were significantly less (p < 0.01) than those of contralateral intact medulla. Therefore, our results showed that ADC and FA values might be a supplementary indicator for determining the severity of AP.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore some of the authors suggest that multi-directional diffusion tensor imaging (DTI) would better imitate the nature of diffusion and thereby structural integrity of tubules. Additionally, one of the advantages of DTI is the capacity of measuring fractional anisotropy of the motion of water, which can be of a specific use in the assessment of the renal medulla [3,11]. …”
Section: Discussionmentioning
confidence: 99%
“…Further, intravoxel incoherent motion (IVIM) is another advanced diffusion imaging approach that differentiates between water motion due to perfusion and diffusion [20, 21]. A body of literature demonstrates that a reduction in ADC or FA correlates with decreased renal function in many renal diseases in human and animals, including chronic kidney disease (CKD) [22, 23], acute kidney injury (AKI) [9, 24], and renal transplantation [25, 26]. Further, recent studies show that renal ADC values correlate with histological measures of fibrosis in patients with CKD and experimental renal disease [22, 2729].…”
Section: Assessment Of Renal Injury and Fibrosismentioning
confidence: 99%